Limitless : upgrade your brain, learn anything faster, and unlock your exceptional life - Kwik, Jim (Hay House, Inc., 2020)
"Let's say you set out to learn a new subject or skill, and you succeed. That's great. You've added to your knowledge and abilities. But it's limited to just that one thing you've learned. Now imagine that instead, the skill you learn is...how to learn. Once you know how to learn-smarter, faster, and better-you can apply it to anything. You can learn to master your mindset or your motivation, or use the methods to pick up martial arts, music, marketing, or Mandarin. Now anything is possible. There are no limits! That's the power Jim Kwik puts in your hands in this remarkable book. For the last 25 years, Jim has helped everyone from celebrities to CEOs to students improve their memory, increase their decision-making skills, learn to speed-read, and unleash their superbrains. Now he shares his revolutionary strategies and shortcuts to help you break free from your perceived limitations and fast-track your fullest potential. In these pages, you'll discover the myths you've been told about your IQ, abilities, and skillset; understand why learning matters; learn core habits and steps to becoming limitless; and explore how you can serve the world"--